Open Science Community Nigeria (OSCN) - Ahmad, Umar Salisu; Bobbo, Khadija Abubakar (My University, 2023)
A presentation we made during our graduation at Open Life Science (OLS) programme. The OLS program is for people interested in applying open principles in their work and becoming Open Science ambassadors in their communities. The slide deck describes our initiative for establishing Open Science Community Nigeria (OSCN) in April 2022 as a scientist-driven nonprofit organisation working to embed open science principles and practices, promote openness, transparency and reproducibility in science among scientists, network of researchers and societal stakeholders in Nigeria. More details can be found in the following links:- Github repo: https://github.com/Open-Science-Community-Nigeria OSCN in Zenodo: https://zenodo.org/communities/oscnigeria/?page=1&size=20
Keywords: Open Science; Transparency; Nigeria